Isolation and Characteristics of Bioflocculant Producing Bacteria from Vannamei Shrimp Ponds - Soedibya, Petrus Hary Tjahja; Setyawan, Agung Cahyo; Palupi, Mustika; Fitriadi, Ren; Nurhafid, Mohammad; Riady, Reza Muhammad (Journal of Advanced Zoology, 2023)
Developing fish farming technology is an urgent research topic to increase fish farming productivity. Global aquaculture production generated about 50 million tons of fish, in 2020, fishery production reached 214 million tons or IDR 424 billion. Aquatic biota production in 2020, 60% higher than the 1990 average, far exceeded world population growth, largely due to increased aquaculture production. One of the technologies used to increase shrimp aquaculture production is biofloc technology. The main aim of this study was to isolate and briefly characterize bioflocculant bacteria from the Vannamei shrimp pond habitat. Research methods included collecting bacteria, isolating bioflocculant-producing bacteria, purifying bacteria, testing bacterial flocculant activity, and identifying bioflocculant bacteria using 16s rDNA. The results showed that 5 isolates showed the highest bioflocculant activity, namely 20.9-44.40%. The five isolates were identified as Vibrio Navarensis, Staphylococcus gallinarum, Pseudoalteromonas ganghwensis, and Cytobacillus kochii. The highest flocculant activity value was obtained by the bacteria Pseudoalteromonas ganghwensis, which was 43%, and Cytobacillus kochii, which was 44.40%. The flocculating activity has the potential as a flocculating agent.